Effect of boiling and stir frying on total phenolics, carotenoids and radical scavenging activity of pumpkin (Cucurbita moschato) - Abdul Hamid, Azizah; Kerk, Chai Wee; Osman, Azizah; Misran, Azizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Effect of various cooking methods on antioxidant content and radical scavenging activity of pumpkin was evaluated. Pumpkin (Cucurbita moschata) was boiled and stir-fried for 2, 4 and 6 minutes respectively. Beta-carotene and lycopene were determined using HPLC and total phenolics measured using Folin-Ciocalteu method. The free radical scavenging activity of the samples was determined using 1, 1-diphenyl-2-picrylhydrazyl assay. Interestingly, result of the study showed an increase in both beta-carotene (2 to 4 times) and lycopene (17 to 40 times) content of pumpkin after cooking for 2, 4 and 6 minutes. However, the treatment resulted in 18 to 54% losses of total phenolics content of the pumpkin. Nevertheless, the free radical scavenging activity exhibited by cooked pumpkins was found to be high, in the range of 81.1% to 94.6% with IC50 of 1.41 to 1.62mg ml-1.